Types and frequency of communication strategies In a bilingual class by a non-English language lecturer - Zubaidi Zubaidi (UPT P2M Politeknik Negeri Malang, 2014)
The objective of this research was to study the communication strategies (CS) used by a non-English lecturer teaching her subject in English. The study was to investigate the types and frequency of CS used by the lecturer and the students’ perception of the use of communication strategies by their lecturer. Data was collected from classroom observations and a questionnaire. Tarone’s (1980) taxonomy of CS was used in this descriptive-qualitative analysis. The results showed that the lecturer used language switch, literal translation, appeal-for-assistance, circumlocution, approximation and message abandonment strategies. Fillers and pauses were also used during her teaching. The students perceived that the use of CS by the lecturer helped them understand the subject better. The strategies that help them to comprehend the lecturer’s explanation better were language switch, literal translation and circumlocution strategy. The students perceived that the use of Indonesian could make understanding easier because their English was still not good.